Penggunaan Instagram @Soloinfo dalam Menyebarkan Informasi di Surakarta Tahun 2023 - Alfajri, Arizka; Sekar Wangi, Maya (Solidaritas, 2024)
This research aims to analyze the use of @soloinfo Instagram account as a medium for disseminating information and references to the community in Surakarta in 2023. This research is a qualitative descriptive research. The object of this research is the @soloinfo Instagram account. Determination of informants in this study using purposive sampling technique, so that the informants of this study consisted of four people, namely Galih Handoko as founder and three informants of Instagram account followers @soloinfo. Instagram account @soloinfo that utilizes Instagram with various Instagram features. The data collection methods used are interview, and documentation. Data analysis was carried out descriptively interactive through the process of data condensation, data presentation, and conclusion drawing. Data validity was tested using triangulation techniques. The results showed that the Instagram account @soloinfo is effective in disseminating information that is easy to understand and visually appealing. The content presented, especially about culinary and events, is well received by followers, as evidenced by interactions in the form of likes, comments, and information sharing. Account managers consistently present accurate and reliable information and schedule posts with regular frequency. The attractiveness of the message is enhanced through the process of content selection, taking and editing photos, and writing informative captions. Thus, the use of Instagram by @soloinfo account is in accordance with its vision in providing information and entertainment to the people of Surakarta. Keywords: Instagram, media, information dissemination, social media